RESPONSE OF BROILER CHICKEN TO INOVO ADMINISTRATION OF DIFFERENT LEVELS OF ROSEMARY OIL(ROSMARINUS OFFICINALIS) - & Tayeb, Sulaiman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was conducted to determine the percentage of hatchability, post-hatch growth performance, immune response of broiler subjected to in- ovo injection of different doses of rosemary oil. A total of 300 eggs of ross broiler strain were obtained.The experiment distributed into five treatment groups: T1, Negative Control T2, positive control (in ovo injection of 0.05 ml distilled water) T3, in ovo injection of 0.05ml of rosemary oil; T4, in ovo injection of 0.075 ml of rosemary oil; T5, in ovo injection of 0.1 ml of rosemary oil.Highest hatchability percentage was shown in 0.1ml rosemary oil -injected hatching eggs. The final weight of birds from 0.075 and 0.1 ml of rosemary oil-injected eggs was significantly (P < 0.05) highest through the experiment. Feed intake and feed conversion ratio were improved with in ovo administration of rosemary oil at 0.075 and 0.1 ml doses. In addition, the level of blood cholesterol and blood glucose were decreased (p<0.05) in birds from rosemary oil-injected eggs. The obtained data showed a positive effect of in-ovo injection of rosemary oil on stimulating bird’s immunity.